Acetate: friend or foe? Efficient production of a sweet protein in Escherichia coli BL21 using acetate as a carbon source - Leone, Serena (Microb Cell Fact, 2015)
BACKGROUND: Escherichia coli is, to date, the most used microorganism for the production of recombinant proteins and biotechnologically relevant metabolites. High density cell cultures allow efficient biomass and protein yields. However, their main limitation is the accumulation of acetate as a by-product of unbalanced carbon metabolism. Increased concentrations of acetate can inhibit cellular growth and recombinant protein production, and many efforts have been made to overcome this problem. On the other hand, it is known that E. coli is able to grow on acetate as the sole carbon source, although this mechanism has never been employed for the production of recombinant proteins. RESULTS: By optimization of the fermentation parameters, we have been able to develop a new acetate containing medium for the production of a recombinant protein in E. coli BL21(DE3). The medium is based on a buffering phosphate system supplemented with 0.5% yeast extract for essential nutrients and sodium acetate as additional carbon source, and it is compatible with lactose induction. We tested these culture conditions for the production of MNEI, a single chain derivative of the sweet plant protein monellin, with potential for food and beverage industries. We noticed that careful oxygenation and pH control were needed for efficient protein production. The expression method was also coupled to a faster and more efficient purification technique, which allowed us to obtain MNEI with a purity higher than 99%. CONCLUSIONS: The method introduced represents a new strategy for the production of MNEI in E. coli BL21(DE3) with a simple and convenient process, and offers a new perspective on the capabilities of this microorganism as a biotechnological tool. The conditions employed are potentially scalable to industrial processes and require only low-priced reagents, thus dramatically lowering production costs on both laboratory and industrial scale. The yield of recombinant MNEI in these conditions was the highest to date from E. coli cultures, reaching on average ~180 mg/L of culture, versus typical LB/IPTG yields of about 30 mg/L. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12934-015-0299-0) contains supplementary material, which is available to authorized users.